2022
DOI: 10.1002/jclp.23439
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness during and after the COVID‐19 pandemic lockdown among Chinese college students: A longitudinal network analysis

Abstract: Introduction In China, recurrent pandemics require frequent city‐wide lockdowns and quarantine actions to contain the impact of COVID‐19, exposing college students to psychological problems, including hopelessness. Hence, the purpose of helping problematic college students alleviate hopelessness symptoms motivates us to carry out the present study to explore their interrelationship. Methods Hopelessness (i.e., a complex phenomenon with important clinical consequences, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
(78 reference statements)
1
14
0
Order By: Relevance
“…The IMV model argued that there were three steps in the emergence of suicidal ideation: defeat – entrapment – suicidal ideation. The COVID‐19 pandemic caused considerable social isolation (Hamza et al, 2021), interpersonal rejection (Mooney & Becker, 2021), challenges in online learning (Adnan, 2020), hopelessness (Tao, Niu, Hou, et al, 2023), the loss of future development opportunities (Lee et al, 2021), financial failure (Nicola et al, 2020), and concerns about personal health and safety (Soria & Horgos, 2021), which are all the roots of feelings of defeat (Turecki & Brent, 2016; Williams et al, 2017). An Indian study (Sripad et al, 2021) found that several early cases of suicide resulting from the impact of COVID‐19 pandemic in India were directly attributed to the stigma and social ostracism associated with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The IMV model argued that there were three steps in the emergence of suicidal ideation: defeat – entrapment – suicidal ideation. The COVID‐19 pandemic caused considerable social isolation (Hamza et al, 2021), interpersonal rejection (Mooney & Becker, 2021), challenges in online learning (Adnan, 2020), hopelessness (Tao, Niu, Hou, et al, 2023), the loss of future development opportunities (Lee et al, 2021), financial failure (Nicola et al, 2020), and concerns about personal health and safety (Soria & Horgos, 2021), which are all the roots of feelings of defeat (Turecki & Brent, 2016; Williams et al, 2017). An Indian study (Sripad et al, 2021) found that several early cases of suicide resulting from the impact of COVID‐19 pandemic in India were directly attributed to the stigma and social ostracism associated with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our results provide information from another facet after quarantine, the relationship between anxiety, depression, and sleep disturbance becomes sparser. In the domain of hopelessness, a factor related to anxiety and depression, Tao et al ( 47 ) drew the same trend in college students, which implied that after quarantine, hopelessness was reduced. Combining previous studies' results, we estimate that less time spent on mobile phones and more physical activities can reduce anxiety, depression, and sleep disturbance and further dilute the bidirectional relationship ( 42 , 48 ).…”
Section: Discussionmentioning
confidence: 92%
“…One point to emphasize is that sad mood is the hallmark symptom needed to meet a diagnosis of major depression ( Fried et al, 2016 ). Fortunately, Tao et al (2022) have revealed through network analysis that the level of hopelessness among college students is significantly reduced once the lockdown ending. Therefore, to intervene in depression development, parents or communities need to understand the situation of students in the lockdown period and address their distorted perceptions.…”
Section: Discussionmentioning
confidence: 99%